7(7-3x)=49

Simple and best practice solution for 7(7-3x)=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(7-3x)=49 equation:



7(7-3x)=49
We move all terms to the left:
7(7-3x)-(49)=0
We add all the numbers together, and all the variables
7(-3x+7)-49=0
We multiply parentheses
-21x+49-49=0
We add all the numbers together, and all the variables
-21x=0
x=0/-21
x=0

See similar equations:

| 8x+11(5+6(3x+7))=4(3x-7) | | x+16=5x-24 | | 7x+4=-3+3x+23 | | -2u+5(u+2)=-5 | | 25=5/7x | | -4+73x-1=59 | | -10v+3v–5=44 | | 8/n-2=6 | | -39=-2v+7(v-7) | | 70=5(6+x)+3x | | 2(a+4)=-16 | | 8+x=6x-27 | | Y=16+y | | 40-5x=45-25x | | -24=3w+3(w+6) | | −2(x−5)=−20 | | 77-2x=90-3x | | 7x/4+8=2x/3-12 | | 7+4x=7x+10 | | 2(w-2)-1=-5(-2w+4)-2w | | 1=10+a/6 | | 102=5x+12 | | 4(7x-1)+3(2-5x)-43x+5)=-6 | | 1=10+a6 | | 3x+33=9x-3 | | 7t+3t=-50 | | 5x-11=5x+ | | -4x+3=7x+102 | | 2a(3a+9)-15=57 | | 5h-5=13=12 | | 53=2u+13 | | -9+7x=x+51 |

Equations solver categories